Dual-Energy CT in the Acute Setting: Bowel Trauma - Wang, Tanche Jimmy; Barrett, Sarah; Ali, Ismail; Khosa, Faisal; Nicolaou, Savvas; Murray, Nicolas (Frontiers in Radiology, 2022)
Traumatic bowel and mesenteric injuries (TBMI) have significant morbidity and mortality. The physical examination is often limited and sometimes not feasible in the trauma patient. Multidetector CT (MDCT) detection of TBMI is challenging and can be life saving. DECT utilizes iodine overlay, monoenergetic imaging and metal artifact reduction to enhance the conspicuity of TBMI. DECT may improve conspicuity of TBMI leading to increased diagnostic accuracy and confidence. The aim of the article is to review the state of the art and applications of DECT in bowel trauma.